Evaluation of some biochemical parameters of pediatric patients hospitalized for rotavirus in Şırnak Province: A retrospective review - Sönmez, Erhan; Tahiroğlu, Veysel; Coşkun, Erkam; Alayunt, Naci Ömer (My University, 2023)
Rotavirus gastroenteritis is an important cause of worldwide morbidity and mortality in infants and children. The main cause of mortality is dehydration due to fluid loss and malnutrition. This study aims to examine the guiding parameters of uric acid and creatinine levels in the detection of dehydration and fluid deficit and inpatient management in cases of rotavirus gastroenteritis. Children who applied to Şırnak State Hospital, Pediatrics Polyclinics, children (6 months-18 years old) whose faecal samples were sent to the laboratory by the research pediatrician considering the diagnosis of rotavirus and whose microbiological examinations were confirmed by immunochromatographic methods (6 months-18 years old), were included in the study by scanning the system. When positive patients were evaluated, the mean age for serum uric acid was 1.06±1.53 and the mean age for serum creatinine was 1.10±1.37. The median value was 3.75 mg/dL in negative patients with serum uric acid levels, and 5.25 mg/dL in positive patients, which was statistically significant (p<0.01). The median value of serum creatinine level was 0.41 mg/dL in negative patients and 0.43 mg/dL in positive patients, which was statistically significant (p<0.05). With this study carried out in Şırnak province, we think that children in the region are severely affected by the rotavirus and face severe dehydration. Therefore, we think that all parameters affected by rotavirus should be evaluated according to regions and parents should be educated about the importance of rotavirus vaccine in the prevention of rotavirus gastroenteritis.
Keywords: Rotavirus; child; creatinine; uric acid